Changes in Sarcoplasmic and Myofibrillar Proteins of Spent Hen and Broiler Meat during the Processing of Surimi-like Material (Ayami) - Babji, Abdul Salam; Gna, Song Kee (Universiti Putra Malaysia Press, 1994)
Spent hens (Rhode Island Red), aged 18 months and broilers (White Leghorn) aged 2 months were processed into a surimi-like material called Ayami. The processing method includes grinding the material twice through a 5mm grinder plate, followed by three steps of washing with ice cold water, after which the washed meat is mixed with cryoprotectants and stored in polythylene bags at - 15°C. Changes in sarcoplasmic and myofibrillar proteins during the processing stages were monitored using the snS-PAGE method. The electrophoretic pattern showed a decrease in intensity in the components of myofibrillar proteins after the first wash, with little changes after the second and third wash. For sarcoplasmic proteins, the intensity of components with molecular weights lower than 100,000 Dalton decreased, whereas the components with molecular weights higher than 100,000 Dalton increased. Washing has significant effects on the sarcoplasmatic and myofibrillar proteins of both spent hen and broiler meat. Such results could explain the gelation properties of surimi-like materials like Ayami.